-2x+y=2...(i)
y=4x-1...(ii)
substitute y in (i)
-2x+(4x-1)=2
-2x+4x-1=2
-2x+4x=2+1
2x=3
2x/2=3/2
x=3/2
replacing x in (ii)
y=4(3/2)-1
y=6-1
y=5
solution=(3/2,5)
x-y+z=6 ...(i)
4y+1=z ...(ii)
3y=2z...(iii)
from(ii),
z=4y+1
substitute z in (iii)
3y=2(4y+1)
3y=8y+2
3y-8y=2
-5y=2
-5y/5=2/5
y=-2/5
substitute y in (ii)
z=4(-2/5)+1
z=-3/5
substitute z and y in (i)
x-y+z=6
x=6+y-z
x=6+(-2/5)-(-3/5)
x=31/5
solution=(31/5,-2/5,-3/5)
-4x+y=-2 ...(i)
y+5=-6x...(ii)
from (i),
y=-2+4x
substitute y in (ii)
(-2+4x)+5=-6x
-2+4x+5=-6x
-2+5=-6x-4x
3=-10x
3/-10=-10x/-10
x=-3/10
substitute x in;;y=-2+4x
y=-2+4(-3/10)
y=-2-6/5
y=-16/5
solution=(-3/10,-16/5)